2012
DOI: 10.1016/s1001-0742(11)60795-x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose production from hydrolysis of cellulose over a novel silica catalyst under hydrothermal conditions

Abstract: A novel silica catalyst was synthesized by evaporation-induced self-assembly (EISA) method and tested for the catalytic selective hydrolysis of cellulose to glucose. This silica catalyst exhibited a higher catalytic activity than other oxides prepared by the same method, such as ZrO 2 , TiO 2 , and Al 2 O 3 . Using silica as a catalyst, cellulose was selectively hydrolyzed into glucose with a glucose yield as high as 50% under hydrothermal conditions without hydrogen gas. The silica catalyst was characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Therefore, the acid strength of all the catalyst fractions was evaluated by using the acidbase titration method. [23] The acidity of MSB (9.38 mmol g À1 ) matched very well with that of pure SMA (9.85 mmol g À1 ). The acidity of the fractions MSF, MSR, and MSS ranged from 4.57 to 5.30 mmol g À1 .…”
Section: Catalyst Characterizationmentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, the acid strength of all the catalyst fractions was evaluated by using the acidbase titration method. [23] The acidity of MSB (9.38 mmol g À1 ) matched very well with that of pure SMA (9.85 mmol g À1 ). The acidity of the fractions MSF, MSR, and MSS ranged from 4.57 to 5.30 mmol g À1 .…”
Section: Catalyst Characterizationmentioning
confidence: 71%
“…The strength of acid sites on the catalyst was calculated by acid-base titration. [23] First, aqueous NaOH solution (0.01 mol/L, 25 mL) was added to a catalyst (0.022 g). Then, the mixture was stirred for 2 h at RT.…”
Section: Characterization Of Catalyst Fractionsmentioning
confidence: 99%
“…The hydrolysis of glycoside also has been explained in [29]. Several articles have been reported on metal oxides such as titanium dioxide (TiO 2 ), silicon oxide (SiO 2 ), zeolite, and ZrO 2 were capable to act as the solid acid catalyst and has been demonstrated as a catalyst in the reaction of converting complex sugar to simple sugar [30,31]. In this method, by using the residue of ZrO 2 to generate acidic condition in the milling jar, will it be possible to break the sugar moiety from asiaticoside to produce asiatic acid.…”
Section: Possible Hydrolysis Mechanism In Millingmentioning
confidence: 99%
“…Heterogeneous catalysis is one of the most effective methods [13,[15][16][17][18][19] and sulfated zirconium dioxide (ZrO 2 ) has been successfully applied to catalyze hydrolysis reactions on cellulose [20,21]. Onda et al [20] have shown highly selective hydrolysis of cellulose into glucose under hydrothermal conditions at 423 K in the presence of sulfonated active carbon (AC-SO 3 H).…”
Section: Introductionmentioning
confidence: 99%